METHANE POTENTIAL AND DEGRADATION KINETICS OF FRESH AND EXCAVATED MUNICIPAL SOLID WASTE IN A TROPICAL LANDFILL (2023)
The optimization of degradation processes and the management of leachate and biogas produced in landfills are key aspects for the establishment of more sustainable municipal solid waste (MSW) disposal in developin countries. In this study, biochemical.